Exploring Microbial Diversity in Forest Litter-Based Fermented Bioproducts and Their Effects on Tomato (Solanum lycopersicum L.) Growth in Senegal - Alexandre Mahougnon Aurel Zoumman; Paula Fernandes; Mariama Gueye; Clémence Chaintreuil; Laurent Cournac; Aboubacry Kane; Komi Assigbetse (International Journal of Plant Biology)
Reducing the use of chemical inputs (fertilizers, pesticides) in agriculture while maintaining crop productivity is the main challenge facing sub-Saharan African family farming systems. The use of effective microorganisms (EM) is among the various innovative approaches for minimizing chemical inputs and the environmental impact of agricultural production and protecting soil health while enhancing crop yields and improving food security. This study sought to characterize the microbial biodiversity of local beneficial microorganisms (BMs) products from locally fermented forest litter and investigate their ability to enhance tomato plant growth and development. Beneficial microorganisms (BMs) were obtained by anaerobic fermentation of forest litter collected in four agroecological regions of Senegal mixed with sugarcane molasses and various types of carbon sources (groundnut shells, millet stovers, and rice bran in different proportions). The microbial community composition was analyzed using next-generation rDNA sequencing, and their effects on tomato growth traits were tested in greenhouse experiments. Results show that regardless of the litter geographical collection site, the dominant bacterial taxa in the BMs belonged to the phyla Firmicutes (27.75–97.06%) and Proteobacteria (2.93–72.24%). Within these groups, the most prevalent classes were Bacilli (14.41–89.82%), α-proteobacteria (2.83–72.09%), and Clostridia (0.024–13.34%). Key genera included Lactobacillus (13–65.83%), Acetobacter (8.91–72.09%), Sporolactobacillus (1.40–43.35%), and Clostridium (0.08–13.34%). Fungal taxa were dominated by the classes Leotiomycetes and Sordariomycetes, with a prevalence of the acidophilic genus Acidea. Although microbial diversity is relatively uniform across samples, the relative abundance of microbial taxa is influenced by the litter’s origin. This is illustrated by the PCoA analysis, which clusters microbial communities based on their litter source. Greenhouse experiments revealed that five BMs (DK-M, DK-G, DK-GM, NB-R, and NB-M) significantly (p < 0.05) enhanced tomato growth traits, including plant height (+10.75% for DK-G and +9.44% for NB-R), root length (+56.84–62.20%), root volume (+84.32–97.35%), root surface area (+53.16–56.72%), and both fresh and dry shoot biomass when compared to untreated controls. This study revealed that forest-fermented litter products (BMs), produced using litter collected from various regions in Senegal, contain beneficial microorganisms known as plant growth-promoting microorganisms (PGPMs), which enhanced tomato growth. These findings highlight the potential of locally produced BMs as an agroecological alternative to inorganic inputs, particularly within Senegal’s family farming systems.